2011
DOI: 10.4315/0362-028x.jfp-10-557
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Total Hydrocyanic Acid Content in Ready-to-Eat Cassava-Based Chips Obtained in the Australian Market in 2008

Abstract: Cassava (Manihot esculenta Crantz) is a widely consumed food in the tropics that naturally contains cyanogenic glycosides (cyanogens, mainly composed of linamarin, acetone cyanohydrin, and hydrocyanic acid). If cassava is not adequately processed to reduce the level of cyanogens prior to consumption, these compounds can lead to the formation of hydrocyanic acid in the gut. Exposure to hydrocyanic acid can cause symptoms ranging from vomiting and abdominal pain to coma and death. In 2008, a survey of ready-to-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Furthermore, even highly processed cassava-based foods can contain residual cyanide. For example, 77 % of the cassava chips tested in Australia exceeded the guideline, with a mean of 64·2 mg HCN equivalents/kg ( 41 , 42 ) . This mean concentration is greater than our cyanide residues after soaking once (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, even highly processed cassava-based foods can contain residual cyanide. For example, 77 % of the cassava chips tested in Australia exceeded the guideline, with a mean of 64·2 mg HCN equivalents/kg ( 41 , 42 ) . This mean concentration is greater than our cyanide residues after soaking once (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, processing of toxic cassava varieties must, in addition to steps to improve shelf-life, include steps that ensure proper removal of the cyanogens (i.e., the glucosides, the cyanohydrins and the HCN) present. The importance of keeping a focus on this was recently illustrated by the finding of relatively high concentrations of total cyanogens in two investigations of traded products in Zambia/Malawi (Nyirenda et al, 2011) and in Australia (Miles et al, 2011), respectively. The latter analysis was of imported ready-to-eat chips.…”
Section: The General Fate Of Cyanogenic Glycosides During Processing mentioning
confidence: 98%
“…The mean concentration was found to be 64.2 mg/kg. The authors stressed that young children are at risk when consuming 100 g of cassava crisps with a HCN concentration of 10 mg/kg (Miles et al, 2011). Authors from another survey in Nigeria also showed their concerns with regard to the consumption of cassava and/or cassava products and the exposure to HCN.…”
Section: Occurrence Datamentioning
confidence: 99%